Meningkatkan Hasil Belajar Siswa Pada Materi Organ Gerak Hewan Pada Mata Pelajaran IPA dengan Menggunakan Media Gambar Pada Siswa Kelas V SDN Sukamulya Kabupaten Pandeglang - Suci Hayati; Rifki Arif Nugraha; Yeni Sulaeman; Ade Farid (Desanta Publisher, 2023)
ABSTRACT The method used in this research is collaborative classroom action research (PTK). Researchers collaborate with teachers to plan, identify, observe and implement the actions that have been designed. The research design used is a spiral system classroom action research using the Hopkins and John Eliot model which begins with preliminary action then continues with planning, action, observation and reflection. The research was carried out in 2 cycles. The research was carried out at SDN Sukamulya, Mekarjaya District, Pandeglang Regency. The samples selected for this research were 25 grade 5 students, consisting of 11 boys and 14 girls. In this research, there were several stages carried out from pre-cycle research, cycle I, and cycle II The results of this research show that in pre-cycle conditions, 1,140 students completed their studies, around 20% of 25 students with a class average of 45.6. After carrying out activities in cycle I, the number of students who completed their studies became 1920 students out of 25 students or around 76% with an average score of 76.8. In cycle II, it was discovered that there were 22 students out of 25 students who had successfully completed their studies, with obtained an average score of 79.2 with a completion percentage of 88% and can be said to be successful. The increase in student learning outcomes in Natural Sciences subjects, animal movement organs, is motivated by the use of effective and fun learning media so that it can motivate students' interest in learning to be even better. The learning media used is image media. Keywords: Student learning outcomes, science lessons, material on animal movement organs, image media.